Pengaruh Risiko Kredit, DPK, Likuiditas Dan Tingkat Efisiensi Usaha Pada Volume Kredit - Fransiska Dewi, Putu Yesi (E-Jurnal Manajemen; Vol 3 No 1 (2014), 2014)
The shift in credit demand indicates BPR in Denpasar experienced credit problems. This is indicated by an increase in loan volume in 2008-2012 but declined in credit growth in 2012. Lending issues examined are the basis of credit risk, deposits, liquidity and the level of business efficiency with volume of credit at 20 rural banks as the sample census method. Secondary data were analyzed using panel data regression analysis with common effect. Hypothesis testing found that decreased credit risk and increased third-party funding and liquidity significantly resulting in increased volume of credit BPR in Denpasar. However,  the increased  level of business efficiency not necessarily lead to increased volume of credit BPR in Denpasar. Keywords : volume of credit, credit risk, third-party funds, liquidity, level of business efficiency
Keywords: volume of credit; credit risk; third-party funds; liquidity; level of business efficiency